Non-canonical DNA in human and other ape telomere-to-telomere genomes - Smeds, Linnéa; Kamali, Kaivan; Kejnovská, Iva; Kejnovský, Eduard; Chiaromonte, Francesca; Makova, Kateryna D (bioRxiv, 2025)
Non-canonical (non-B) DNA structures-e.g., bent DNA, hairpins, G-quadruplexes (G4s), Z-DNA, etc.-which form at certain sequence motifs (e.g., A-phased repeats, inverted repeats, etc.), have emerged as important regulators of cellular processes and drivers of genome evolution. Yet, they have been understudied due to their repetitive nature and potentially inaccurate sequences generated with short-read technologies. Here we comprehensively characterize such motifs in the long-read telomere-to-telomere (T2T) genomes of human, bonobo, chimpanzee, gorilla, Bornean orangutan, Sumatran orangutan, and siamang. Non-B DNA motifs are enriched at the genomic regions added to T2T assemblies, and occupy 9-15%, 9-11%, and 12-38% of autosomes, and chromosomes X and Y, respectively. G4s and Z-DNA are enriched at promoters and enhancers, as well as at origins of replication. Repetitive sequences harbor more non-B DNA motifs than non-repetitive sequences, especially in the short arms of acrocentric chromosomes. Most centromeres and/or their flanking regions are enriched in at least one non-B DNA motif type, consistent with a potential role of non-B structures in determining centromeres. Our results highlight the uneven distribution of predicted non-B DNA structures across ape genomes and suggest their novel functions in previously inaccessible genomic regions.